Moderation Values in Arabic Classrooms: Perspectives of Secondary School Teachers - Sobri, Muhammad; Supian, Supian; Sanusi, Anwar; Mustofa, Ady Muh. Zainul; Hasani, Salman (Universitas Islam Negeri Raden Intan Lampung, 2025)
As a core subject in Islamic schools, Arabic language education holds strategic potential to promote moderation values through linguistic and moral engagement. This role becomes increasingly vital amid growing concerns about intolerance and exclusivism among students in Indonesia. This study aims to analyze how Arabic language teachers at Islamic Junior High Schools (MTs) in Muaro Jambi internalize and operationalize the values of religious moderation in their classroom practices—particularly in the initial, core, and closing learning activities. This study employed a qualitative approach, utilizing a case study design that incorporated interviews, classroom observations, and document analysis. The results showed that the values of religious moderation in Arabic language learning in the classroom were reflected in every stage of learning. In the core activities, teachers instructed students to discuss in small groups while studying al-qirā’ah (reading) and al-kitābah (writing). This discussion instilled the values of shūrā (deliberation) and iṣlāḥ (improvement). When differences of opinion arose, the teacher emphasized politeness and respect, reflecting tasāmuḥ (tolerance), and provided a direct example of behavior (qudwah). The implication is the need for the development of contextual Arabic language teaching materials, along with moderation and teacher training, to make the integration of these values more systematic and sustainable.